EXPLORING GEN-Z STUDENTS’ PROBLEMS AND ATTITUDES IN SPEAKING ENGLISH - Raysha Davinna; Angelina Monthesari; Gabby Maureen Pricilia; Reni Afifah Harahap; Rizky Harahap (Jurnal Education and Development, 2026)
The purposes of this research are to find out: (1) To identify the common problems encountered by Gen Z students in speaking English, (2) To analyze the factors caused students problem in speaking English, (3) To explore the attitudes of students in speaking English. The method of the research descriptive qualitative research. The informant of this research is all third semester students of English Language Education Study program at Institut Pendidikan Tapanuli Selatan with total 18 students. The instruments to collect the data are questionnaires and interview. The results revealed students experienced significant affective problems such as anxiety, fear of making mistakes, shyness and lost-of self-confidence; social aspect include role of parents class environment and learning community; instructional aspect like use of mother tongue, teacher low commands in speaking English and teacher speaking time; linguistically, students struggled with lack of vocabulary pronunciation, and grammar While the factors cause the problems are afraid of being judge, anxious, and effected pronunciation in English by mother tongue. Despite these challenges, students exhibited positive cognitive and behavioral attitudes, recognizing the importance of English speaking and actively participating when supported, although affective barriers moderated their oral performance. The study highlights the interconnectedness of Generation Z characteristics, such as digital-nativeness and social sensitivity, with conventional speaking problems and attitudes.